The big year [videorecording (DVD)] - Martin, Steve, 1945-; Black, Jack, 1969-; Wilson, Owen, 1968-; Cleese, John; Pike, Rosamund, 1979-; Dennehy, Brian; Wiest, Dianne; Williams, JoBeth; Huston, Anjelica; Jones, Rashida; Obmascik, Mark (Twentieth Century Fox Home Entertainment, 2011)
"Looking to shake up their routine lives, three amateur bird watchers compete to become the ultimate 'birder' by spotting the greatest number of species within a single calendar year. But the friendly rivalry soon turns into a hilariously complicated cross-country adventure as each man begins to realize that the quest for success comes at a price--and that's not chicken feed!"--Container.